(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
In this article, the necessity and mechanisms for organizing the movement of vehicles to the city of Samarkand without entering the city center (from 1075+590 km of the M-39 "Almaty - Bishkek - Tashkent - Shakhrisabz - Termez" highway) along external bypass roads (from 0 km of the R-48 highway) were developed. In particular, foreign experience in this area was analyzed, and proposals suitable for the city of Samarkand were selected. Traffic jams occurring in the city, their causes have been identified, and modern solutions have been developed to prevent them. The necessity of introducing an automated digital control system on the main access roads located within the city limits, directing traffic through bypass roads, and developing a digital monitoring system is scientifically substantiated.